Karakteristik Pembakaran Premixed Campuran Bioetanol Dan Premium (Gasoline) - Riwu, Defmit B.N.; Tobe, Adi Y.; Adoe, Dominggus G. H.; Pah, Jack C.A.; Baria, Metrisno (Universitas Nusa Cendana, 2022)
Bioethanol is one of the renewable energies that can be used as fuel. Ethanol produced from palm sap can be used to mix fuel oil (BBM) into gasohol (energy mixed) which marks green fuels era begin. This research was conducted by burning a mixture of Bioethanol (105 ml, 120 ml, 135 ml, 143 ml) and Premium (45 ml, 30 ml, 15 ml, 7 ml), to determine the effect of adding Premium into bioethanol on temperature and flame color. The combustion process is carried out by premixed, in which a mixture of bioethanol and premium is heated to produce steam. This steam will be given a spark to produce combustion of the mixture. After the steam burns and produces a fire, then the air flow rate is regulated until the fire is blow-off. The results of the study indicate that, if the composition of bioethanol in the fuel is increasing, the flame looks bluer and the equivalence ratio value becomes smaller. In addition, the temperature reached at point 1 is higher than point 2. This indicates that point 1 is the final combustion zone, which is where the fuel has been burned completely